Random systems in ultrametric spaces. (1st February 2019) - Dawson, D. A.; Gorostiza, L. G.
Abstract: We discuss percolation and random walks in a class of homogeneous ultrametric spaces together with similarities and differences in ultrametric and Euclidean spaces. We briefly outline the role of these models in the study of interacting systems. Several open problems are presented.